FS: fraction solution / Leong Siow Hoo, Voon Li Li and Nor Hazizah Julaihi - Leong, Siow Hoo; Voon, Li Li; Julaihi, Nor Hazizah (Universiti Teknologi MARA, Kedah, 2023)
Fraction is one of the most important topics for learners to build a solid foundation to be successful in related concepts such as ratio, proportion, rate, probability and beyond. However, it is a topic that worldwide students struggle, especially on fraction arithmetic. The lack of understanding is then translated into difficulties with advanced mathematics, and other related subjects and applications. The main drawback of the existing teaching aids for fraction is that they are emphasizing the understanding of individual fractions, but not fraction arithmetic. An innovative teaching aid termed Fraction Scale (FS) is proposed to address the problem. The FS aims to provide visual representation of various concepts of fraction including fraction arithmetic. An experiment was conducted in two sub-urban primary schools to test the effectiveness of FS. During the sessions, the concepts of fraction were introduced using the FS according to the lesson plan designed specifically for FS. The results show that the scores of fraction arithmetic in post-test are higher than the pre-test for all the three types of fraction problems given. The feedback from the students reveals that the design of FS is user-friendly and helps them to understand fraction arithmetic. Hopefully, FS contributes to the efforts of achieving the nation’s target of 60:40 Ratio Policy in which the enrolment of students in science and technical stream is sixty percent. The commercialization potential of FS is great as the topic of the fraction is in the syllabi of elementary education worldwide.